A System Analysis of Cold Storage using the New Non-Freon Refrigerant GF-08 - Shun Kataniwa; Kiyoshi Dowaki (Chemical Engineering Transactions, 2020)
The equipment for chilling or freezing food consumes much energy. Therefore, there is a need to reduce the energy consumption. Also, to contribute to reduce the greenhouse gas (GHG) emissions, it is necessary to replace conventional refrigerants which affect Global Warming because of high Global Warming Potential (GWP). Hence, there is a need for the use of alternative refrigerants with lower GWPs. Therefore, in this study, the potential of the non-freon refrigerant GF-08, which consists of hydro-carbons, as an alternative refrigerant was evaluated. The use of GF-08 for chilling and freezing storage systems was evaluated. The eco-benefits of GF-08 in comparison to the conventional refrigerant (R404A) was evaluated by developing a theoretical simulation model. A demo-test using a refrigerator in a restaurant was conducted to validate the simulated result. This result showed that performance differences depend on different operating conditions of temperature. Based on the simulation model, the benefits considering the energy reduction was evaluated. The reduction of the annual energy consumption, and the environmental impact of GF-08 using the life cycle assessment (LCA) methodology were estimated. The use of GF-08 reduced the annual energy consumption by 28.6% and the GHG emissions by 27.1 % in comparison to the R404A.